The numbers I have input, it’s seems like the answer is never.
Answer:
- ![\frac{61}{11}](https://tex.z-dn.net/?f=%5Cfrac%7B61%7D%7B11%7D)
Step-by-step explanation:
=
( cross- multiply )
6x = 5y ( divide both sides by 6 )
x =
y
Then
← substitute x =
y into the expression
= ![\frac{\frac{25}{6}y+6y }{\frac{25}{6}y-6y }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B25%7D%7B6%7Dy%2B6y%20%7D%7B%5Cfrac%7B25%7D%7B6%7Dy-6y%20%7D)
= ![\frac{\frac{61}{6}y }{-\frac{11}{6}y }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B61%7D%7B6%7Dy%20%7D%7B-%5Cfrac%7B11%7D%7B6%7Dy%20%7D)
= ![\frac{\frac{61}{6} }{-\frac{11}{6} }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B61%7D%7B6%7D%20%7D%7B-%5Cfrac%7B11%7D%7B6%7D%20%7D)
=
× - ![\frac{6}{11}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B11%7D)
= - ![\frac{61}{11}](https://tex.z-dn.net/?f=%5Cfrac%7B61%7D%7B11%7D)
Answer:
D
Step-by-step explanation: